Rorty On Religion - NUR, ABDULLAH SELMAN (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Philosophy, 2020)
This thesis aims to explore Rorty's pragmatic approach to religion and critically engage with it. In the core of this approach lies his distinction between private and public projects, and his plea for the privatization of religion. Rorty argues that private beliefs do not need to be justified to others. They are about one's own making sense of the world, and individuals are under no obligation, neither epistemological nor moral, to justify them to other people. He insists that religious beliefs should be construed and understood as private beliefs. Throughout the thesis, I analyse the details and the implications of this position. I engage with the ethics of belief debate and examine the robustness of Rorty's views on unjustified private beliefs. I engage with his pragmatic predecessors and explore their influences on Rorty. I investigate his stance on religion's place in public. I discuss his views on democracy in relation to his views on religion. Finally, I compare his pragmatic approach to its current, mainstream alternatives. I conclude that Rorty offers a novel, attractive way to think and talk about religion. His approach is tolerant enough to accommodate both theistic and atheistic orientations. It is also robust enough to be able to fend its critics off.
APPROVED
Keywords: Richard Rorty; Pragmatism; Religion; Philosophy of Religion; Private vs Public